Laboratory Diagnostic Approach and Interpretation in Gram-Negative Bacterial Infection: A-Case Report of Sepsis in Secondary Hospital Settings - Adhi Kristianto Sugianli; Ida Parwati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Gram-Negative Bacteria (GNB) have been widely reported to cause worldwide infections and life-threatening. The high prevalence of drug-resistant GNB causes the treatment of GNB to become difficult. This case report describes a stepwise laboratory approach and interpretation for Gram-negative bacteria infection in sepsis patients. An 84-year-old female patient with a history of congestive heart failure, after three weeks of hospitalization, GNB was proven as the cause of sepsis. Laboratory approach for inflammation (C-reactive protein, procalcitonin) was made and confirmed with a positive culture of several specimens (sputum, urine, and blood). The identification of bacterial-culture revealed as Carbapenem-resistance Klebsiella pneumoniae and Extended-spectrum Beta-lactamases Escherichia coli. This case highlights GNB as a potential agent to worsen the infection (sepsis) and also a useful approach for the detection of multidrug-resistant bacteria, particularly in secondary hospital settings. The application and interpretation of integrated clinical and laboratory criteria may bring out better and effective patient management.